A vivência comum dos afetos: arte, biopotência e servidão biodiaconal - Oliveira, José Carlos de (2022)
The issue of freedom and servitude has always been a theme addressed by political philosophy. Nevertheless, in this research, such matter is approached, mainly, regarding the fields of ethics, politics, and esthetic. In effect, the artistic creation can be a freeing ethical-political strategy, but it can also become an instrument used to keep both the individual and the collective in a position of subservience. When favoring freedom, art is at the service of biopotency, when used to reinforce servitude and passivity, it is at the service of biodeaconry. The theoretical ground for the concepts of biopotency and biodeaconry anchors itself, mainly, in Foucault, Spinoza and Vygotsky. By addressing the human being capacity of persevering in existence, the relationship between body and mind, the affective dynamics - which can both increase or decrease the body power to act and the mind power to reflect - and imagination as something inherent to human existence, Spinoza presents some important parameters to the development of art as a resistance strategy. Likewise, Vygotsky has contributed to the development of the concept of biopotency, especially when he discusses the common experience of affections, the catharsis, the creativity, and the dialectical relationship between the individual and the collectivity. From Foucault, the main inspiring concepts towards our biodeaconry approach are: biopolitics, biopower and government techniques, both from oneself and others'. Regarding the empirical aspect, some interviews were held with professionals who work in different activities, but also perform in theater, dance, and music. The accounts presented by interviewees have shown that there is a dialectical relationship between biodeaconry and biopotency, given the fact that experiencing affections in the process of artistic creation confronts the affective-volitional experiences in the workspace. In creation processes, an increase in the power of life is observed, however, in the workspace, the biodeaconry, in its eagerness to conform body and mind to the existing structures, restrains transformation movements. In this sense, there is a contradiction between what is lived in art and what is lived, daily, in the institutional context. Effectively, when art can strengthen the ordinary, instead of producing a mere esthetic effect, it also produces ethical-political strategy actions. By being able to unite everyone in the search of common usefulness, art cooperates towards the increase in a common effort to persevere in existence. In this sense, theater, dance, and performance, by producing stronger emotions, contrary to those produced by the biodeaconry dynamics, transform themselves in active resistance strategies. On the other hand, when these artistic practices become a place of contagion for emotions or mere entertainment, then, they reinforce servitude and not freedom, diluting, dispersing, or restraining the transforming power of life